TARAS SALYGA: “IT’S ME, WHO GOES TO ITSELF...” TO TARAS SALYGA ON AN ANNIVERSARY - BARAN, Ye. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Article is devoted to creation of Taras Salyga.